Evaluation of methylenetetrahydrofolate reductase gene variant (C677T) as risk factor for bipolar disorder - Rai, V. (Cellular and Molecular Biology, 2011)
Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme in the metabolism of folate, whose role in bipolar disorder is controversial. The aim of the present study was to assess the risk of MTHFR C677T polymorphism for bipolar disorder. The author performed a meta-analysis and pooled data from individual case-control studies that examined the association between C677T polymorphism and bipolar disorder (meta-analysis: 8 studies, 1457 cases and 2169 controls).The pooled Odd Ratios (OR) were estimated by both fixed effects and random effects models. The meta-analysis with fixed effects showed that there was 71% heterogeneity between the eight studies. The fixed effect pooled OR was 1.07 (95% CI; 0.98 to 1.17) and Cochran Q was 24.13 (df = 7; p=0.0011). The study is significant and shows meager association. The random effect pooled OR was 1.07(95% CI; 0.87 to 1.32) and Cochran Q was 24.13 (df = 7; p=0.0011). The random effect pooled OR was also significant and shows meager association between MTHFR C677T genotype and bipolar disorder.